Enhancement of unsteady frequency responses of electro-thermal resonance MEMS cantilever sensors. Issue 1 (March 2021) - Setiono, Andi; Nyang'au, Wilson Ombati; Fahrbach, Michael; Xu, Jiushuai; Bertke, Maik; Wasisto, Hutomo Suryo; Peiner, Erwin
Abstract: Unsteady frequency response of in-plane electro-thermal MEMS-based cantilever sensors can cause up-/down-shifting of the resonance phase, which becomes an inhibitive factor in resonance locking using a phase-locked loop setup. Moreover, the inconsistency of resonance phase during real-time measurement potentially causes inaccuracy in resonant-frequency locking. In this work, reference parameters are differentially subtracted from the sensor output signals to enhance the characteristic of frequency response. As a calculation result, a constant resonance phase can be successfully achieved by adjusting the reference parameters close to the sensor baseline, both in sensor amplitude and phase.